URGENSI PENGATURAN TERHADAP PENYALAHGUNAAN ARTIFICIAL INTELLIGENCE PADA TINDAK PIDANA MALWARE DI INDONESIA - Putri, Wilianli Melati Jaya; Berlian, Cheny; Yuniarti, Rahmi; Dinata, Umar (LPPM, Universitas Muhammadiyah Riau, 2025)
The misuse of Artificial Intelligence in malware crimes is a serious challenge in the digital era, considering that Artificial Intelligence can be used to create more sophisticated and difficult to detect malware. The urgency of regulating the misuse of Artificial Intelligence is very important to prevent the potential for widespread losses in the cyber sector. This study examines the forms and impacts of the misuse of Artificial Intelligence in malware crimes and the urgency of regulating the misuse of Artificial Intelligence in malware crimes in Indonesia. The research method used is normative juridical with a comparative legal approach. The results of the first discussion show that the forms of misuse of Artificial Intelligence have increasingly developed, including Adaptive Malware, Smart Phishing, Artificial Intelligence Powered Ransomware, Artificial Intelligence Powered Botnets, Polymorphic Malware, Spyware Artificial Intelligence, and Artificial Intelligence Powered Worms, then discuss the legal impacts that arise and most often are related to criminal liability due to the misuse of Artificial Intelligence in malware crimes. Second, the results of the discussion show that Indonesia does not yet have specific regulations regarding the misuse of Artificial Intelligence in cybercrime. On the other hand, the European Union has established an Artificial Intelligence Act with a risk-based approach, while China regulates Artificial Intelligence through strict administrative provisions.